Self-reported frequency of handwashing among pet and non-pet owners in different situations: results of four surveys of the general adult population in Germany - Karolin M. E. Nettelrodt; Thomas von Lengerke (BMC Public Health)
Abstract Background Zoonotic diseases are partly associated with pets. However, data is sparse on pet owners’ compliance with preventive recommendations. Also, research focuses on self-reports, which are subject to overestimation biases, i.e., assessing one’s actual performance to be better than it is. One reason is task difficulty: people tend to overestimate their performance on hard tasks. Regarding handwashing, compliance after touching animals should be harder for pet vs. non-pet owners due to the number of opportunities. This study tests for differences in self-reported handwashing between pet and non-pet owners, and explores reasons for non-compliance. Thus, it aims to provide insights on how to improve self-report behavioral assessment methods in public health and One Health research. Methods Data from cross-sectional computer-assisted telephone surveys of the general population in Germany aged 16–85 years in 2012, 2014, 2017 and 2019 were analyzed (N = 15,559; response rate: 45.9%). Handwashing frequency was operationalized for nine indications using the item “How often do you wash your hands in each of the following situations: ‘never/almost never‘, ‘seldom‘, ‘mostly‘, ‘always/almost always‘?”, with the latter defining compliance. In 2017 and 2019, those reporting to ‘never/almost never‘ or ‘rarely‘ wash hands were questioned regarding possible reasons. Chi²-tests, Cohen’s d’s and multiple logistic regressions were used. Results Pet and non-pet owners differed in self-reported handwashing compliance primarily in the indication “After touching animals” (35.5% vs. 55.7%, effect size: d = 0.45). For other indications (e.g., “After using the toilet”), differences were insignificant (≤|3.6%|, d ≤ 0.11). Additionally, 79% of pet owners who rarely or almost never washed their hands after touching animals felt it is not necessary (non-pet owners: 67.1%; d = 0.34). Reporting to not have an appropriate washing facility available was rarer among pet owners (44.5% vs. 63%, d = 0.41). Differences regarding other reasons were trivial (d ≤ 0.16), including “It takes too long” (16.9 vs. 13.3%; p = .138 in multiple regression). Conclusions Study limitations include that due to unknown true compliance, over- and underestimations have to be inferred. Yet, that the only substantial difference between pet and non-pet owners pertained to „After touching animals” suggests such effects. While pet owners obviously adjust for task difficulty, the likely residual overestimation should be reduced by measures using script-based covert recall or survey items with response categories constructed to better resemble subjective compliance ratios.